2018
DOI: 10.1016/j.matdes.2018.07.044
|View full text |Cite
|
Sign up to set email alerts
|

A feasible method of support slimming based on the different thresholds of polar angles in selective laser melting

Abstract: The large thermal deformation induced by the high temperature gradient severely restricts the threshold level of polar angle in selective laser melting (SLM). As such, different types of support structures are usually added to improve the manufacturing capacity and broaden the application of SLM technology. However, enormous support structures will result in large time consumption, material waste, high labor intensity and inferior surface quality of part. In this research, a feasible method of slimming support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Laser additive manufacturing is a technological method for the direct production or growing of functional objects from powders. Recent research [1][2][3][4] has aimed to create new classes of materials as gradient construction and functional materials (with gradient properties for different functional elements of geometrically complex parts), gradient reinforced by ceramics [5], variations of content for intermetallic alloys, adaptations of the method for hard-to-melt materials as hard alloys based on tungsten or tungsten itself, etc. [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Laser additive manufacturing is a technological method for the direct production or growing of functional objects from powders. Recent research [1][2][3][4] has aimed to create new classes of materials as gradient construction and functional materials (with gradient properties for different functional elements of geometrically complex parts), gradient reinforced by ceramics [5], variations of content for intermetallic alloys, adaptations of the method for hard-to-melt materials as hard alloys based on tungsten or tungsten itself, etc. [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The viability of producing an overhang without support structures with various overhang angles was first investigated, followed by the proposal of a method for generating reduced support structures using varying polar angle requirements. The results revealed an average reduction of 35% in support infrastructure [20]. Vanek et al proposed a novel method for reducing the number of support structures required for overhanging surfaces created with Fused Deposition Modeling (FDM) technology.…”
Section: Introductionmentioning
confidence: 99%
“…Takaichi et al [18] found that the fatigue strength of supported specimens was more than twice that of unsupported specimens. Zhang et al [19] developed a feasible method of slimming support structures and used this method to eliminate the quantities of their support structures by 35% on average. Song et al [20] proposed functionally graded support structures and found that these structures can maintain a higher temperature level than conventional uniform support structures, which is equivalent to an extra preheating effect and can also reduce distortion.…”
Section: Introductionmentioning
confidence: 99%